Dual crystal x-ray spectrometer at 1.8 keV for high repetition-rate single-photon counting spectroscopy experiments. (22nd August 2016) - Gamboa, E.J.; Bachmann, B.; Kraus, D.; MacDonald, M.J.; Bucher, M.; Carron, S.; Coffee, R.N.; Drake, R.P.; Emig, J.; Ferguson, K.R.; Fletcher, L.B.; Glenzer, S.H.; et al.
Abstract: With the recent development of high-repetition rate x-ray free electron lasers (FEL), it is now possible to perform x-ray scattering and emission spectroscopy measurements from thin foils or gasses heated to high-energy density conditions by integrating over many experimental shots. Since the expected signal may be weaker than the typical CCD readout noise over the region-of-interest, it is critical to the success of this approach to use a detector with high-energy resolution so that single x-ray photons may be isolated. Here we describe a dual channel x-ray spectrometer developed for the Atomic and Molecular Optics endstation at the Linac Coherent Light Source (LCLS) for x-ray spectroscopy near the K-edge of aluminum. The spectrometer is based on a pair of curved PET (002) crystals coupled to a single pnCCD detector which simultaneously measures x-ray scattering and emission in the forward and backward directions. The signals from single x-ray photons are accumulated permitting continuous single-shot acquisition at 120 Hz.